Systems of organic farming in spring vetch II: Biological response of Aeolothrips intermedius Bagnall and Coccinella septempunctata L - Nikolova, Ivelina; Georgieva, Natalia (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
The effects of four systems of organic farming of spring vetsch on Aeolothrips intermedius Bagnall (Thysanoptera: Aeolothripidae) and Coccinella septempunctata L. (Coleoptera: Coccinellidae) population density and the toxicity of several products on predatory insects were studied. The variants were: Control (without using any biological products); combined treatment with Polyversum (biological foliar fertilizer) and Biofa (biological plant growth regulator); treatment with NeemAzal T/S (biological insecticide, a.i. azadirachtin) and treatment with a combination of NeemAzal with Polyversum and Biofa. Variant V was a conventional farming system in which a combination of Nurelle D (synthetic insecticide), Masterblend (foliar fertilizer) and Flordimex 420 (growth regulator) was used as a standard treatment. In the organic farming system that included treatment of plants with the biological insecticide NeemAzal (azadirachtin), the reduction in A. intermedius abundance was 20.7% when it was applied alone and 24.6 % in combination with the organic products Polyversum and Biofa. NeemAzal achieved a lower reduction in the counts of predatory ladybirds C. septempunctata, from 14.9% (alone) to 21.9% (combination). The biological insecticide, applied alone or in combination, was mostly harmless and rarely harmful to A. intermedius. NeemAzal manifested harmlessness to C. septempunctata as its toxic action did not exceed 25%. An analysis of variance regarding product toxicity to A. intermedius and C. septempunctata demonstrated that the type of treatment (the application of insecticides alone or in combination) had the strongest effect on product toxicity. Тhe use of neem-based insecticides can be a substantial contribution towards preservation of biodiversity in ecosystems.